Relevant Issues of Epidemiological Safety Provision as Regards Natural-Focal Infections during the XXII Olympic and XI Paralympic Winter Games in Sochi - B. P. Kuz’Kin; E. B. Ezhlova; A. N. Kulichenko; O. V. Maletskaya; Yu. V. Demina; T. V. Taran; N. D. Pakskina; O. N. Skudareva; N. F. Vasilenko; T. V. Kharchenko; E. A. Manin; G. M. Grizhebovsky; et al. (Проблемы особо опасных инфекций, 2015)
The paper contains the data on the morbidity rates as regards natural-focal infectious diseases and results of epizootiological monitoring in the locality of the XXII Olympic and XI Paralympic Winter Games-2014 in Sochi. It is demonstrated that the significant ones in the infectious disease incidence chart are hemorrhagic fever with renal syndrome, Ixodidae tick-borne borrelioses, pseudotuberculosis, intestinal yersiniosis, leptospiroses, rabies, rickettsiosis, and tularemia. Represented are the data on the peculiarities of a number of regional pathogenic strains. Noted is fact that complex activities, which were carried out by the agencies and institutions of the Rospotrebnadzor, Krasnodar Territory and Sochi resort-town Administration, allowed for the stabilization of the situation on natural-focal infections.